KEPASTIAN HUKUM DALAM PERHITUNGAN PPh AKAD IJARAH MUNTAHIYAH BITTAMLIK - Muh Yassir Akbar Ramadhani (Al-Amwal : Journal of Islamic Economic Law, 2021)
Agreement of Ijarah Muntahiyah Bittamlik is a rent buy contract in sharia banking. But, it creates problem for sharia banking because there is multiple interpretations at Regulation of Ministry of Finance No.136/PMK.03/2011 about imposition of tax income for business activities in Islamic Fincancing. The aim of research is to know type of legal interpretation which use by account representative to calculate income tax from Ijarah Muntahiyah Bittamlik’s agreement and also the theory that use to make interpretation of account representative become even. Research method which use is normative method with conseptual approach. The result is account representative use authentic legal interpretation and extensive interpretation. As for theory that can use for even the interpretation is legal certainty by way of merge Regulation of Ministry of Finance No.136 and No.137. Other than that, it need to be held training of statutory techniques so that legal interpretation of account representative becomes even.Key words: legal interpretation, legal certainty, income tax, agreement of ijarah muntahiyah bittamlik.